AB1232 RHEUMA-VOR: A PROOF-OF-CONCEPT NETWORK STUDY FOR THE IMPROVEMENT OF RHEUMATOLOGICAL HEALTH CARE THROUGH COORDINATED COOPERATION. (June 2019) - Dreher, Matthias; Assmann, Gunter; Hoeper, Kirsten; Triantafyllias, Konstantinos; Zeidler, Jan; Binder, Harald; Schmitt, Reinhold E.; Schwarting, Andreas
Abstract : Background: Rheumatoid arthritis (RA), psoriasis arthritis (PsA) and spondyloarthritis (SpA) are the most common chronic autoimmune rheumatic diseases. For all 3, the so-called "window of opportunity" [1-3] has been identified as the decisive factor affecting the outcome. Objectives: The aim of the prospective study is to improve early diagnosis of RA, PsA and SpA and thus positively impact the quality of care for patients with the help of coordinating centers. The primary endpoint is the number of cases with an actual indication for immediate referral to a specialist in proportion to all reported cases. Methods: The project establishes a network of the University Medical Center Mainz, the Medical School Hannover, the Center for Rheumatology Lower Saxony e.V., the University Medical Center Saarland, the ACURA Center of Rheumatology Rhineland-Palatinate, the Leibniz University Hannover and the University Medical Center Freiburg, local rheumatology specialists, the associations of statutory health insurance physicians and general practitioners and the 3 regional associations of the Deutsche Rheuma-Liga e.V. Covering 3 federal states, the network reaches approximately 13 million inhabitants. Primary care providers are given access to screening questionnaires to document potential early cases of RA, PsA, and SpA, based on characteristic symptoms. These are evaluated by multidisciplinary teams at the regional coordinating centers. If they fulfill the criteria for referral, patients get an appointment at a cooperating rheumatology specialist within weeks. If a rheumatic disease is diagnosed, physicians and patients receive questionnaires on sociodemographic data, quality of life, functionality, medication, diagnosis and psychological aspects. After 12 months, the questionnaires are completed a second time. The collected data is compared with a matched reference group of the German Rheumatism Research Center. It is planned to screen up to 8.700 people within the 30-month survey phase that started in October 2017. Results: Preliminary data will be presented at the conference. Currently, 2.400 patients have been screened, of which 400 patients were included in the study and 15 already underwent their follow-up screening. Conclusion: Previous studies have shown positive results of coordinated cooperation among the relevant care providers. For example, 75 percent of the patients diagnosed with early RA within the ADAPTHERA network were in remission after 2 years (DAS28<2.6) [4]. Corresponding developments are expected in all clinical pictures for participants in Rheuma-VOR. References: [1] O'Dell, J.R., Treating rheumatoid arthritis early: a window of opportunity? Arthritis Rheum, 2002. 46(2): p. 283-5. [2] Boehncke, W.H. and A. Menter, Burden of disease: psoriasis and psoriatic arthritis. Am J Clin Dermatol, 2013. 14(5): p. 377-88. [3] Claudepierre, P., Spondyloarthritis: a window of opportunity? Joint Bone Spine, 2014. 81(3): p. 197-9. [4] Lauter, A., et al. ADAPTHERA - Landesweit transsektorales Versorgungsnetzwerk für Patienten mit früher rheumatoider Arthritis zeigt anhaltende Remissionen in der Regelversorgung. Wunder Punkt: Die Triage. (2018). Manuscript. Disclosure of Interests: Matthias Dreher: None declared, Gunter Assmann: None declared, Kirsten Hoeper: None declared, Konstantinos Triantafyllias: None declared, Jan Zeidler: None declared, Harald Binder: None declared, Reinhold E. Schmitt: None declared, Andreas Schwarting Grant/research support from: GSK, Pfizer, AbbVie, Novartis, Roche, Speakers bureau: GSK, Novartis